Gene Expression Pattern and Protein Localization of Arabidopsis Phospholipase D Alpha 1 Revealed by Advanced Light-Sheet and Super-Resolution Microscopy - Novák, Dominik; Vadovič, Pavol; Ovečka, Miroslav; Šamajová, Olga; Komis, George; Colcombet, Jean; Šamaj, Jozef (Frontiers in Plant Science, 2018)
Phospholipase D alpha 1 (PLDα1, At3g15730) and its product phosphatidic acid (PA) are involved in a variety of cellular and physiological processes, such as cytoskeletal remodelling, regulation of stomatal closure and opening, as well as biotic and abiotic stress signalling. Here we aimed to study developmental expression patterns and subcellular localization of PLDα1 in Arabidopsis using advanced microscopy methods such as light-sheet fluorescence microscopy (LSFM) and structured illumination microscopy (SIM). We complemented two knockout pldα1 mutants with a YFP-tagged PLDα1 expressed under the PLDα1 native promoter in order to study developmental expression pattern and subcellular localization of PLDα1 in Arabidopsis thaliana under natural conditions. Imaging of tissue-specific and developmentally-regulated localization of YFP-tagged PLDα1 by LSFM in roots of growing seedlings showed accumulation of PLDα1-YFP in the root cap and the rhizodermis. Expression of PLDα1-YFP in the root rhizodermis was considerably higher in trichoblasts before and during root hair formation and growth. Thus, PLDα1-YFP accumulated in emerging root hairs and in the tips of growing root hairs. PLDα1-YFP showed cytoplasmic subcellular localization in root cap cells and in cells of the root transition zone. In aerial parts of plants PLDα1-YFP was also localized in the cytoplasm showing enhanced accumulation in the cortical cytoplasmic layer of epidermal non-dividing cells of hypocotyls, leaves and leaf petioles. However, in dividing cells of root apical meristem and leaf petiole epidermis PLDα1-YFP was enriched in mitotic spindles and phragmoplasts, as revealed by co-visualization with microtubules. Finally, super-resolution SIM imaging revealed association of PLDα1-YFP with both microtubules and clathrin-coated vesicles (CCVs) and pits (CCPs). In conclusion, this study shows the developmentally-controlled expression and subcellular localization of PLDα1 in dividing and non-dividing Arabidopsis cells.